Back to normal : why ordinary childhood behavior is mistaken for ADHD, bipolar disorder, and Autism Spectrum Disorder - Gnaulati, Enrico (Boston : Beacon Press, 2013)
Why are doctors, teachers, and parents incorrectly diagnosing healthy American children with serious psychiatric conditions? Gnaulati examines the factors that have led to our current crisis, provides parents with information about symptoms that to a casual or untrained eye can mimic a psychiatric disorder, and gives parents of struggling children hope, perspective, and direction.
A veteran clinical psychologist exposes why doctors, teachers, and parents incorrectly diagnose healthy American children with serious psychiatric conditions.
Mad science and mad medicine -- The rush to diagnose -- Casualties of casual diagnosing -- Abnormalizing boys -- The normalcy of problem behavior -- ADHD or childhood narcissism at the outer edges? -- Bipolar disorder? or teenage storm and stress twenty-first-century style? -- Autistic spectrum? or a brainy, willful, introverted boy? -- Parenting with authority.
Includes bibliographical references and index.
Keywords: Behavior disorders in children; Behavior disorders in children -- Diagnosis; Child Behavior -- psychology; Adolescent; Behavioral Symptoms -- diagnosis; Child; Diagnostic Errors; Medicalization; Mental Disorders -- diagnosis; Behavior disorders in children; Behavior disorders in children -- Diagnosis